Golgijev aparat - Erdani-Kreft, Mateja (Medicinski razgledi, 2013)
The Golgi apparatus is a cellular organelIe found in most eukaryotic cells. In addition to its participation in protein and lipid glycosylation, the Golgi apparatus also sorts and directs vesicular transport. The number ofknown diseases related to the Golgi apparatus has significantly increased in last decade because of the developments in genetic analysis and discoveries which showed that glycan structures are not mere decorative elements of proteins and lipids but serve crucial cellular functions. Improper function ofthe Golgi apparatus is the cause of various congenital and acquired disorders of glycosylation as well as numerous neurodegenerative diseases. Recently, the importance of the Golgi apparatus transformation during celI division, celI differentiation and celI death bas been discovered. Understanding of the Golgi apparatus is important for more effective detection and treatment of diseases associated with the Golgi apparatus. Since the Golgi apparatus is involved in many cellular process es, it is also suitable as a target for pharmaceuticals. In this review, some facts about the Golgi apparatus' structure and functions are summarized and the influence of the Golgi apparatus in various diseases is discussed.
Keywords: Golgi apparatus; Golgijev aparat; intracellular transport; znotrajcelični transport; diferenciacija; differentiation